Tracking and characterization of convective cells through their maturation into stratiform storm elements using polarimetric radar and lightning detection - Hu, Jiaxi; Rosenfeld, Daniel; Zrnic, Dusan; Williams, Earle; Zhang, Pengfei; Snyder, Jeffrey C.; Ryzhkov, Alexander; Hashimshoni, Eyal; Zhang, Renyi; Weitz, Richard (Atmospheric research, 2019)
Polarimetric radars make it possible to retrieve information on hydrometeors types, sizes and concentrations. Additional information on cloud electrification can be obtained from Lightning Mapping Arrays (LMAs). To study the development time and height of the hydrometeors and electrification require tracking their evolution within the lifecycle of convective cells. A new methodology for multi-cell identification and tracking (MCIT) is presented in this study. The algorithm in this study is different from traditional tracking methods; this new algorithm is applied to time series of radar volume scans. It tracks local maxima of vertically integrated liquid (VIL) water by identifying the two cells in consecutive radar scans that have maximum common VIL. The vertical profile of the polarimetric variables is used for constructing the time-height cross section of the cells' microphysical properties around the peak reflectivity as a function of height. The LMA sources that occur within the cell area are integrated as a function of height as well for each time step, as determined by the radar volume scans. The result of the tracking can provide insights on the evolution of storms, hydrometer types, precipitation initiation and cloud electrification under different thermodynamic and aerosol conditions. The details of the MCIT algorithm, its products and their performance for different type of storms are described in this paper. •Development of a novel cloud cell tracking algorithm.•Tracking cloud types include: convective and stratiform, isolated and clustered.•Tracking cloud cells through maturation into stratiform storm elements.•Use a synergy of polarimetric radar, satellite, lightning detection and model data.•Algorithm has flexible output options and possibilities for further studies.